India - Swachh Bharat Mission Support Operation : Fiduciary Systems Assessment - World Bank (Washington, DC, 2016)
A fiduciary systems assessment (FSA) was carried out to evaluate the arrangements relevant to the operation and to determine whether they provide reasonable assurance that the operation funds will be used for their intended purpose. Taking into account the improvements required and the agreement on the actions required to strengthen the systems (which are reflected in the program action plan (PAP), the overall fiduciary framework is considered adequate to support the operation management and to achieve the desired results. Assessments have been carried out in five states through two consulting firms. PricewaterhouseCoopers Private Limited (PwC) was engaged to carry out assessments in West Bengal and Odisha, while Ernst and Young Limited (E and Y) were engaged for assessments in Chattisgarh, Madhya Pradesh, and Rajasthan. The overall objective of the operation is to accelerate efforts under swachh Bharat mission gramin (SBM-G) to achieve universal sanitation coverage, enhance cleanliness, and eliminate open defecation in rural areas by leveraging Bank funds to incentivize performance of the states and, to increase ministry of drinking water and sanitation (MDWS) capacity to facilitate states in program implementation. The proposed operation will support the national program over a five year period (2015-2020); coinciding with the timeframe of the national program. To strengthen the program’s procurement implementation capacity, several crucial measures should be adopted including additional staffing, intensive training, and hiring of qualified procurement and contract management support consultants, and robust procurement audit. The Bank will also provide assistance and support to the program implementation and will closely monitor the program procurement performance.